The effect of finansial rations on the firm value - I Made Suidarma; Kadek Ovy Satyawati; I Putu Denny Dwipayana; I Nyoman Arta Yasa (Faculty of Economics and Business Mulawarman University, 2022)
This study aims to determine the effect of profitability, liquidity, and firm size on firm value with firm size as a moderating variable in the consumer sector non-cyclical listed on the IDX for the period 2019-2021. The population of this research is all issuers that are included in the non-cyclical consumer sector, purposive sampling used to select samples so as to produce a total of 31 samples. Using SPSS 26 to process data, the results of this study indicate that profitability has a significant influence with a positive influence on firm value, liquidity and firm size do not have a significant effect. If viewed simultaneously, profitability, liquidity, and firm size have a significant influence on firm value. As a moderating variable, based on research results, capital structure has not been able to strengthen or weaken the relationship between profitability, liquidity, and firm size to firm value.